Inside Back Cover: Algae: A natural active material for biomedical applications (View 4/2021). Issue 4 (29th August 2021) - Zhong, Danni; Du, Zhen; Zhou, Min
Abstract : As a natural resource, microalgae has been explored as a novel biological material, and has been widely used in the field of biomedicine. In article number 20200189, Min Zhou and coworkers display that microalgae offers outstanding potential for multiple diagnostic and therapeutic applications, including bioanalysis, tissue engineering, wound healing, drug delivery and hypoxia‐associated tumor therapy.